Cavity Vertex Regeneration through Optimal Energy Model for Restoration of Worn Parts - Jian Gao; Xiangping Zeng; Xu Zhang; Xin Chen; Detao Zheng (Institute of Advanced Engineering and Science, 2013)
Restroration of worn parts is a key technique in remanufacturing engineering. It is also a popular research topic in the domain of sustainable manufacturing. To tackle the difficult problem of obtaining a reference model for repair of worn parts, this paper proposed a novel approach to regenerate the vertices over the worn cavity. After a brief description of the repair process, this paper focuses on the optimal energy model establishment. Based on the energy model the vertices of the worn cavity can be regenerated. Error calculation of the vertices recreated to the original model is proposed to search the shortest distance. These algorithms proposed were implemented in the repair system through Visual C++6.0. Several examples of worn parts are presented to illustrate the feasibility of the method. The testing result shows that the vertex regenerated through the optimal energy model can satisfy the requirement of accurate geometry regeneration for repair of worn parts. Finally, conclusions are drawn and further research work is discussed. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2479